(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
As an integral part of settlement pattern, rural areas are considered one of the primary components of territorial organization of society. The changes taking place in the latter have a siginificant impact on various processes of social development. Contemporary tendencies analysis and current problems revelation of RA rural settlement pattern transformation have been done in the article, solutions have been pointed out as well.